Research Commentary—Cooperation, Coordination, and Governance in Multisourcing: An Agenda for Analytical and Empirical Research - Bapna, Ravi; Barua, Anitesh; Mani, Deepa; Mehra, Amit (Information Systems Research, 2010)
Multisourcing, the practice of stitching together best-of-breed IT services from multiple, geographically dispersed service providers, represents the leading edge of modern organizational forms. While major strides have been achieved in the last decade in the information systems (IS) and strategic management literature in improving our understanding of outsourcing, the focus has been on a dyadic relationship between a client and a vendor. We demonstrate that a straightforward extrapolation of such a dyadic relationship falls short of addressing the nuanced incentive-effort-output linkages that arise when multiple vendors, who are competitors, have to cooperate and coordinate to achieve the client's business objectives. We suggest that when multiple vendors have to work together to deliver end-to-end services to a client, the choice of formal incentives and relational governance mechanisms depends on the degree of interdependence between the various tasks as well as the observability and verifiability of output. With respect to cooperation, we find that a vendor must not only put effort in a “primary” task it is responsible for but also cooperate through “helping” effort in enabling other vendors perform their primary tasks. In the context of coordination, we find that task redesign for modularity, OLAs, and governance structures such as the guardian vendor model represent important avenues for further research. Based on the analysis of actual multisourcing contract details over the last decade, interviews with leading practitioners, and a review of the single-sourcing literature, we lay a foundation for normative theories of multisourcing and present a research agenda in this domain.